2007
DOI: 10.3147/jsfp.42.29
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Kuchijirosho Associated Proteins by Western Blot with Sera of Tiger Puffer which Survived Kuchijirosho

Abstract: ABSTRACT-Kuchijirosho (snout ulcer disease) is an infectious disease of tiger puffer Takifugu rubripes in Japan and Korea. Little is known about detailed characteristics on the causative agent of kuchijirosho, except it is a filterable agent. In the present study, kuchijirosho associated proteins (KAPs) with molecular weight of 100 -120 kDa were detected in brain tissues of tiger puffer by western blot analysis with sera of tiger puffer which survived kuchijirosho, but not in the kidney or spleen tissues. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Inouye (1988) indicated that the kuchijirosho virus is a DNA virus because, when a homogenate of kuchijirosho-affected fugu brain was treated with DNase, the infectivity of the pathogen of kuchijirosho was completely lost. Although the symptoms of kuchijirosho caused by infection with kuchijirosho virus used in this study are similar to those described in other reports (Hatai et al, 1983;Nakauchi et al, 1985;Wada et al, 1985Wada et al, , 1986Inoue et al, 1986Inoue et al, , 1992Miyadai et al, 2001;Takami et al, 2007aTakami et al, , 2007bTakami et al, , 2007c, more than one virus species might be involved in the development of kuchijirosho. We detected KARs in fugu showing symptomatic signs similar to kuchijirosho that had broken out at an aquaculture farm in 2020 in Japan (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Inouye (1988) indicated that the kuchijirosho virus is a DNA virus because, when a homogenate of kuchijirosho-affected fugu brain was treated with DNase, the infectivity of the pathogen of kuchijirosho was completely lost. Although the symptoms of kuchijirosho caused by infection with kuchijirosho virus used in this study are similar to those described in other reports (Hatai et al, 1983;Nakauchi et al, 1985;Wada et al, 1985Wada et al, , 1986Inoue et al, 1986Inoue et al, , 1992Miyadai et al, 2001;Takami et al, 2007aTakami et al, , 2007bTakami et al, , 2007c, more than one virus species might be involved in the development of kuchijirosho. We detected KARs in fugu showing symptomatic signs similar to kuchijirosho that had broken out at an aquaculture farm in 2020 in Japan (Fig.…”
Section: Discussionsupporting
confidence: 90%